Potential Inhibitors of Fascin From A Database of Marine Natural Products: A Virtual Screening and Molecular Dynamics Study - Lin, Lirui; Lin, Kai; Wu, Xiaodong; Liu, Jia; Cheng, Yinwei; Xu, Li-Yan; Li, En-Min; Dong, Geng (Frontiers in Chemistry, 2021)
Marine nature products are unique compounds which are produced by marine environment including plants, animals and microorganisms. The wide diversity of marine nature products is found to be versatile, especially for drug discovery. In this paper, we use state-of-the-art computational methods to discover inhibitor from marine nature products to block the function of Fascin, an overexpressed protein in various cancers. First, virtual screening (pharmacophore model and molecular docking) carried out based on the marine nature products database (12015 molecules) and it gives eighteen molecules those inhibit the function of Fascin potentially. Next, molecular mechanics generalized Born surface area (MM/GBSA) calculations indicate that four molecules have higher binding affinities than the inhibitor NP-G2-029, which has been validated experimentally. Moreover, ADMET analyses of pharmacokinetics demonstrate one of the four molecules does not match the criterion. Finally, ligand Gaussian accelerated molecular dynamics (LiGaMD) simulations are carried out to validate the three inhibitors binding to Fascin stably. In addition, dynamic interactions between protein and ligands are analyzed systematically. Our study will accelerate development of the cancer drugs targeting Fascin.